Sistem Kontrol Kendali Mesin Roll Forming Baja Ringan di PT. Primaland Pandeglang - Anggito Wito Utomo; Desmira Desmira (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The light steel roll forming machine is a tool used in the manufacturing industry to continuously shape steel sheets into specific profiles. Efficiency and accuracy in production heavily depend on the control system employed. This article discusses the implementation of an automatic control system in a light steel roll forming machine, focusing on the use of sensors, actuators, and a microcontroller-based control system. Additionally, the system is equipped with a digital printing machine to directly print product branding and light steel specifications. The research results indicate that the application of an automatic control system enhances product precision, improves production efficiency, and reduces the defect rate.